2022
DOI: 10.1002/etc.5284
|View full text |Cite
|
Sign up to set email alerts
|

Emerging contaminant exposure to aquatic systems in the Southern African Development Community

Abstract: The growing production and use of chemicals and the resultant increase in environmental exposure is of particular concern in developing countries where there is rapid industrialization and population growth but limited information on the occurrence of emerging contaminants. Advances in analytical techniques now allow for the monitoring of emerging contaminants at very low concentrations with the potential to cause harmful ecotoxicological effects. Therefore, we provide the first critical assessment of the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…One decade ago, ecotoxicology was a relatively new science in South Africa (Wepener & Chapman, 2012 ), but it has developed rapidly, and nowadays, numerous studies can be found on ecotoxicological risk assessment of aquatic systems in the SADC region, with large differences between countries (Eijsackers et al, 2020 ; Selwe et al, 2022 ). Future investigations concerning freshwater quality should link chemical and bioanalytical information and quantify cause-effect relationships (Altenburger, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…One decade ago, ecotoxicology was a relatively new science in South Africa (Wepener & Chapman, 2012 ), but it has developed rapidly, and nowadays, numerous studies can be found on ecotoxicological risk assessment of aquatic systems in the SADC region, with large differences between countries (Eijsackers et al, 2020 ; Selwe et al, 2022 ). Future investigations concerning freshwater quality should link chemical and bioanalytical information and quantify cause-effect relationships (Altenburger, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As CECs and other potential EDCs enter the environment, target screening alone is not enough to determine their effects (Hashmi et al, 2020). Moreover, there is a growing concern regarding transformation products because changes in chemical structures may subsequently result in bioactivity and environmental impacts (Selwe et al, 2022). Non‐target or suspect screening can be done by high‐resolution mass spectrometry to determine the transformation products in environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…), toothpaste, makeup or cosmetics, laundry detergent, and sunscreen. 25 , 37 For instance, pharmaceuticals are employed by both humans and animals to reduce the risk of disease, enhance the quality of meat, or increase the rate of reproduction. Since they are employed to improve the health of plants, animals, and people, and because they are partially disintegrated in the environment, many of them end up in water bodies, soil, or sewage.…”
Section: Sources Of Eeccsmentioning
confidence: 99%